A transmissive concentrator photovoltaic module with cells directly cooled by silicone oil for solar cogeneration systems. (15th April 2021) - Ji, Yaping; Artzt, Luke E.; Adams, Will; Spitler, Christopher; Islam, Kazi; Codd, Daniel; Escarra, Matthew D.
Highlights: PV converts short-wave light to electricity and transmits remainder for thermal use. Silicone oil removes waste heat, flowing past immersed cells in concentrated light. Prototype tested outdoors for 572 sun·hrs at up to 166 suns with PV module < 120 °C. A conical cavity thermal receiver collects the transmitted infrared light. Hybrid receiver shows 86% efficiency (electricity, cell cooling, and thermal power). Abstract: Hybrid concentrator photovoltaic-thermal systems can cogenerate electricity and heat by beam-splitting incoming concentrated light onto photovoltaic cells and a thermal receiver to increase total conversion efficiency and potentially reduce system cost. To demonstrate this, we have designed and prototyped a transmissive spectrum-splitting concentrator photovoltaic module that maximizes solar energy conversion by utilizing the entire solar spectrum. Visible light is collected using infrared-transmissive triple-junction photovoltaic cells to achieve an in-band module efficiency of 43.3% for light of wavelength λ < 873 nm, while 44.2% of out-of-band light with λ > 873 nm is transmitted through for collection by a thermal receiver. During testing on a dual-axis tracked parabolic concentrator dish at up to 166 suns, cell temperatures were maintained at 119 °C or below via a novel active cooling method. This cooling system strictly flows silicone oil directly across both sides of the cells, without inhibiting optical transmission, as verified through experimentation and simulation. The module was validated outdoors for 572 sun·hrs, and achieved a maximum thermal receiver temperature of 180 °C. 86.1% of incident solar power is collected at 166 suns average concentration collectively among the electrical, cooling, and thermal receiver subsystems. The remaining 13.9% is lost to mirror reflectivity, dish shadowing, receiver reflection, and thermal losses. The ability to directly cool the cells with an inert silicone oil offers the potential for reduced system cost relative to previous transmissive hybrid concentrator photovoltaic-thermal systems, including microfluidic-cooled designs. This solar cogeneration capability is valuable in a wide range of commercial and industrial applications.